APLIKASI BANTU BELAJAR GRAMMAR BAHASA INGGRIS BERBASIS ANDROID - Fajar, Riki Isken Koto Rangkik; Hellyana, Corie Mei; Pratama - Universitas Bina Sarana Informatika, Eva Argarini (Indonesian Journal of Networking and Security (IJNS), 2020)
Abstract - As we know, English in Indonesia is currently an important language and must be learned especially by students. But English is also like Indonesian language which has grammar or pronunciation of words properly and correctly, if English we call grammar. Basically grammar is a set of structured rules that govern the arrangement of sentences, phrases and words in any language Grammar or grammar is very important in English. But some people only learn grammar in their schools. Therefore the Android-based English grammar learning application is made so that students can learn English at any time, anytime and anywhere. This application can only run on Android-based smartphones. This application is made as easy as possible in the application there are some materials and there are also some practice questions for later application users to answer these questions. The English grammar learning application is expected to be an alternative medium in learning and understanding English grammar or grammar properly. Keywords— Application, Grammar, English Abstrak - Seperti yang kita ketahui, bahasa inggris di Indonesia saat ini merupakan bahasa yang penting dan harus di pelajari khusunya oleh pelajar atau mahasiswa. Namun bahasa inggris juga seperti bahasa Indonesia yang memiliki tata bahasa atau pengucapan kata dengan baik dan benar, jika bahasa inggris kita sebut grammar. Pada dasarnya grammar adalah himpunan dari aturan yang terstruktur yang mengatur susunan kalimat, frase, dan kata dalam bahasa apapun Grammar atau tata bahasa sangatlah penting dalam berbahasa Inggris. Namun beberapa orang hanya belajar grammar di sekolahnya saja. Maka dari itu dibuatlah Aplikasi belajar grammar bahasa inggris berbasis Android agar pelajar dapat belajar bahasa inggris setiap waktu, kapanpun dan dimanapun. Aplikasi ini hanya dapat berjalan di smartphone yang berbasis Android. Aplikasi ini dibuat semudah mungkin didalam aplikasi terdapat beberapa materi dan juga terdapat beberapa latihan soal untuk nantinya pengguna aplikasi menjawab soal tersebut. Aplikasi belajar grammar bahasa inggris ini diharapkan bisa menjadi media alternatif dalam mempelajari dan memahami grammar atau tata bahasa inggris dengan baik dan benar. Kata kunci— Aplikasi, Grammar, Bahasa Inggris